Madness and Rulers: Events in Coorg and London in 1810, as observed by the Hon. Arthur Cole, the resident at Mysore - Jain, Sanjeev (Indian J Psychiatry, 2015)
What happens if a King becomes mentally ill? Excerpts from the personal papers of Arthur Henry Cole, Resident to the Kingdom of Mysore in 1809, open up fascinating insights into the madness of rulers, in neighboring Coorg and faraway London, and ways in which different societies responded to this. Musings on legal capacity and restrictions imposed on account of insanity, as well as migration and ennui in imperial colonies inevitably follow.